SOSIALISASI PEMILU 2024 BAGI PEMILIH PEMULA SEBAGAI MANIFESTASI DEMOKRASI DALAM LINGKUNGAN KAWAN SEBAYA - Nababan, Kristina Roseven; Listiarum, Febri; Efendi, Muhammad (Universitas Kristen Satya Wacana Salatiga, 2024)
The first-time voters represent the young generation who are exercising their right to vote for the first time. Given their substantial numbers, particular attention needs to be devoted to them in the upcoming 2024 general elections. This endeavour aims to provide socialization on the electoral process for the 2024 General Elections to first-time voters within the University, Church Youth, and community settings. The dissemination of information will be conducted through interactive activities, discussions, and the provision of easily comprehensible and relevant information. Additionally, this research will encompass assistance in verifying the Permanent Voter List (DPT) to ensure that first-time voters are correctly registered and can exercise their voting rights accurately in the forthcoming elections. Through these efforts, first-time voters will gain a deeper understanding of the significance of participating in the democratic process and will be equipped with adequate knowledge about the electoral procedures, thus enabling them to make informed decisions concerning the nation's future.